On the scopal interaction of negation and deontic modals - Iatridou, Sabine (Proceedings of the Amsterdam Colloquium, 2009)
In this paper we argue that the different scopal relations that deontic modal auxiliaries cross-linguistically exhibit can be explained by assuming that (i) polarity effects arise in the domain of universal deontic modals and therefore not in the domain of existential deontic modals; and (ii) that all deontic modals must be interpreted VP in situ if their polarity requirements allow for that.